Coordinate Clause of Compound Declarative Sentence in CBS News - Budiarta, Putu Thania Auginitha; Maharani , Putu Devi; Putra , I G B Wahyu Nugraha (Journal of Language and Applied Linguistics, 2024)
The objective of this study is focused on analysing and determining the kinds of coordinate clause of compound declarative sentence in CBS News that related to article of education in the past six months. Observation and documentation method were applied for collecting the data of this study. On the other hand, this study applied two methods for analysing and determining the data found, there were formal method to present the result and informal method to determine the data found. The data found in this study was used the theory that proposed by Davidson (2002). For the result, this study has found 38 sentences containing coordinate clause of compound declarative sentence. There were two kinds of coordinate clause of compound declarative sentence from the data source: coordinate clause without conjunction or use punctuation is a comma (4), coordinate clause with conjunction “and” (20), “but” (6), “or” (4), “so” (3), “nor” (1).